PENGEMBANGAN MULTIMEDIA UNTUK PENGENALAN TOKOH WAYANG DALAM PEMBELAJARAN BAHASA JAWA - Aulia Fithri Nurlaili; Heri Suwignyo; Punadji Setyosari (Graduate School of Universitas Negeri Malang, 2016)
The introduction of the puppet characters for elementary school students is difficult to do, because the students are not interest to story and puppet characters. The purpose of this study, produce multimedia for the introduction of puppet characters are valid, practical, effective, and attractive, so it can be easier for students to recognize the puppet characters. This research is development research, the development model Lee and Owens (2004) with step coherent and easy to follow, step this model is: analysis, design, development, implementation, evaluation. The results showed that the level of validity reached 85.35%; practicability rate 89%; the level of effectiveness of 93.2%; the attractiveness of the level of 88.15%. Suggestions for improvement experts into consideration product improvement. So that the resulting fit product for use with improvements in certain parts.Pengenalan tokoh wayang kepada siswa sekolah dasar memang sulit dilakukan, hal ini dikarenakan tidak tertariknya siswa terhadap cerita dan tokoh wayang. Tujuan penelitian ini menghasilkan multimedia untuk pengenalan tokoh wayang yang valid, praktis, efektif, dan menarik, sehingga dapat memudahkan siswa untuk mengenal tokoh wayang. Penelitian ini merupakan penelitian pengembangan, dengan model pengembangan Lee dan Owens (2004) dengan langkah yang runtut dan mudah untuk diikuti, yaitu analisis, desain, pengembangan, implementasi, evaluasi. Hasil penelitian menunjukkan bahwa tingkat kevalidan mencapai 85,35%; tingkat kepraktisan 89%; tingkat keefektifan 93,2%; tingkat kemenarikan 88,15%. Saran perbaikan para ahli menjadi pertimbangan perbaikan produk sehingga produk yang dihasilkan layak digunakan dengan perbaikan pada beberapa bagian tertentu.